ANALYSIS OF THE ATTITUDES OF UNIVERSITY LIBRARIANS TOWARDS LIBRARY SERVICES: A THEORY OF PLANNED BEHAVIOR APPROACH - Dwi Utari Fajariah; Rizka Pitri; Reza Nawafella Alya Parangu (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
University library service effectiveness is heavily influenced by the psychological dynamics and quality of interaction between librarians and users. However, limited human resources often lead to high workloads and emotional fatigue, reducing responsiveness during peak hours. This study analyzes university librarians' attitudes toward circulation and reference services and identifies their underlying factors using Icek Ajzen’s Theory of Planned Behavior (TPB) framework. Employing a qualitative descriptive method, data were gathered through direct observations, in-depth interviews with librarians at the Institute of Informatics and Business (IIB) Darmajaya Bandar Lampung, documentation, and data triangulation from the library’s suggestion box reports. The integration of TPB indicators reveals distinct behavioral patterns: under attitude toward the behavior, librarians successfully cultivate a welcoming environment through standard greeting courtesies; however, excessive workloads and multitasking significantly diminish service responsiveness during peak periods. Under subjective norms, structured guidance from superiors and a collaborative peer environment serve as vital social pressures that enforce librarian professionalism. Regarding perceived behavioral control, continuous professional training provided by the Indonesian College Library Forum (FPPTI) serves as an essential external resource that enhances librarians' emotional regulation and self-efficacy when handling diverse user characters. The study concludes that while structural constraints impair operational speed, social support and professional training effectively reinforce positive psychological controls and professional attitudes in library services.